The end of oil : on the edge of a perilous new world - Roberts, Paul (Boston : Houghton Mifflin, 2004)
This work is an investigation of the way oil dominates our lives and what is likely to happen when it runs out.
Includes bibliographical references (p. 350-358) and index.
oif 11/02/15
Loan
Keywords: Petroleum industry and trade - political aspects; Petroleum industry and trade - government policy; Energy policy; Petroleum industry and trade; World politics - forecasting; United States